2020
DOI: 10.1590/198053147264
|View full text |Cite
|
Sign up to set email alerts
|

Comissões De Heteroidentificação Racial Para Acesso Em Universidades Federais

Abstract: Resumo O artigo analisa a política de cota racial para acesso à educação superior em uma universidade federal brasileira em seu mais recente ajuste: a instalação de uma comissão de heteroidentificação racial que se baseia no fenótipo dos(das) candidatos(as). A base epistemológico-metodológica parte de uma análise crítica da política, entendendo que a construção dessa ação pública é fruto de embates e disputas entre atores com diferentes concepções de justiça social. O resultado da pesquisa aponta que, na unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…Finally, organizations are subject to the influence of activists working within them, broader social movements (Davis, McAdam, Scott, and Zald, 2005), and other stakeholders. Case studies have shown that black activism was instrumental in the adoption of procedures to validate the racial self-declarations (Batista, Figueiredo, 2020;Dias, Tavares Junior, 2018;Guimarães, Rios, Sotero, 2020;Leite, 2020;Marques, 2019;Oliveira, 2019;Silva, Cirqueira, Rios, Alves, 2020). To understand how this happened, we have sought to identify the channels through which demands formulated by social movements reached policymakers (Lavalle, Carlos, Dowbor, Szwako, 2018;Rios, 2018) and the judiciary and the results that ensued.…”
Section: Changing Universitiesmentioning
confidence: 99%
“…Finally, organizations are subject to the influence of activists working within them, broader social movements (Davis, McAdam, Scott, and Zald, 2005), and other stakeholders. Case studies have shown that black activism was instrumental in the adoption of procedures to validate the racial self-declarations (Batista, Figueiredo, 2020;Dias, Tavares Junior, 2018;Guimarães, Rios, Sotero, 2020;Leite, 2020;Marques, 2019;Oliveira, 2019;Silva, Cirqueira, Rios, Alves, 2020). To understand how this happened, we have sought to identify the channels through which demands formulated by social movements reached policymakers (Lavalle, Carlos, Dowbor, Szwako, 2018;Rios, 2018) and the judiciary and the results that ensued.…”
Section: Changing Universitiesmentioning
confidence: 99%
“…Por fim, as organizações estão sujeitas à influência de ativistas atuando no seu interior e de movimentos sociais mais amplos (Davis et al, 2005), assim como de outros grupos interessados. Estudos de caso mostraram que o ativismo negro foi importante para a adoção de procedimentos de validação das autodeclarações raciais (Batista, Figueiredo, 2020;Dias, Tavares Júnior, 2018;Guimarães, Rios, Sotero, 2020;Leite, 2020;Marques, 2019;Oliveira, 2019, Silva et at., 2020. Para compreender como isso aconteceu, procuramos identificar os canais pelos quais as demandas formuladas por movimentos sociais chegaram aos formuladores das políticas (Lavalle et al, 2018;Rios, 2018) e ao judiciário, e os resultados disso.…”
Section: Universidades Em Transformaçãounclassified
“…9. For the case studies, see Silveira 2015;Santos et al 2019;Elísio et al 2019;Marques et al 2019;Maciel et al 2019;Fonseca and Costa 2019;Dias and Tavares Júnior 2018;Passos 2019;Nunes 2019;Miranda et al 2020;Silva et al 2020;Silva and Custódio 2021;Silva and dos Santos 2021;Rodrigues 2022;. [Batista and Figueiredo 2020?…”
Section: Notesmentioning
confidence: 99%
“…Asked to be certain about their identities, or phenotypes, and knowing that they will have to pass in front of a commission may lead those who are less familiar with repertoires of blackness (and more familiar with traditional repertoires of racial democracy) to self-exclude. Although there are no conclusive results about that idea, Batista and Figueiredo (2020) found that the number of applicants who self-identify as preto and pardo has declined since commissions were implemented at a federal university in the South.…”
Section: Seeing and (Re)making Race Through Verification Commissionsmentioning
confidence: 99%